Robbins PATHOLOGIC BASIS OF DISEASE - Cotran, Ramzi S.; Kumar, Vinay; Robbins, Stanley L.; Schoen, Frederick J. (W.B. SAUNDERS COMPANY : Philadelphia, 1994)
This new edition has been revised and updated. It maintains the same author team, who provide state-of-the-art coverage of the pathological basis of disease.
Includes index
Bibliography : pages 1354-1356
Keywords: Pathology